2019
DOI: 10.3390/rs11070825
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Irrigated Areas of Northeast China in Comparison to Natural Vegetation

Abstract: Accurate information about the location and extent of irrigation is fundamental to many aspects of food security and water resource management. This study develops a new method for identifying irrigation in northeastern China by comparing canopy moisture between the cropland and adjacent natural ecosystems (i.e., forests). This method is based on two basic assumptions, which we validated using field survey data. First, the canopy moisture of irrigated cropland, indicated by a satellite-based land surface water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Satellite remote sensing has proven its high capability and effectiveness for mapping and monitoring irrigated areas [8][9][10]. Recent studies have shown that irrigated areas could be spatially quantified over large scale using either passive optical sensors [11][12][13] or active radar sensors [14][15][16]. Optical images has been widely used to map irrigated areas using the difference between the spectral signature of irrigated crops and that of non-irrigated crops in the time series domain.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite remote sensing has proven its high capability and effectiveness for mapping and monitoring irrigated areas [8][9][10]. Recent studies have shown that irrigated areas could be spatially quantified over large scale using either passive optical sensors [11][12][13] or active radar sensors [14][15][16]. Optical images has been widely used to map irrigated areas using the difference between the spectral signature of irrigated crops and that of non-irrigated crops in the time series domain.…”
Section: Introductionmentioning
confidence: 99%
“…The overall accuracy for detecting irrigation water supplements reached 87%. Recently, Xiang et al [19] mapped irrigated areas of northeast China by comparing the MODIS derived LSWI (Land Surface Water Index) of the agricultural areas to the surrounding natural vegetation such as forests. They assumed that the canopy moisture indicated by the LSWI is higher for irrigated crops than the adjacent forest.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of accurate ground-truth measurements and high spatio-temporal EO data prevent the researchers from examining environmental objectives, such us the irrigation activities, the organic farming, the soil properties and the nitrogen balance in terms of land degradation risk, or the assessment of the greenhouse gas (GHG) and ammonia (NH3) emissions. Exceptions are the studies of Paredes-Gómez et al 16 , Xiang et al 25 and Alexandridis et al 26 , who tried to provide accurate information about the location and the extent of irrigated areas, leveraging both satellite-based multispectral data (e.g. ASTER, SPOT-4, Landsat 7 ETM+, MODIS, and Sentinel-2A & -2B) and other ancillary data, such as cumulative precipitation measurements, and digital elevation models (DEM).…”
Section: Earth Observation Contribution In the Modernized Cap Objectivesmentioning
confidence: 99%